Proximate composition and cost benefit analysis of smoked Clarias gariepinus and Oreochromis niloticus treated with some natural spices (Agriculture, Food, and Natural Resources Journal, 2025)
This study evaluated the impact of smoking combined with natural spices (salt, clove, garlic, and ginger) on the nutritional value and profitability of Clarias gariepinus and Oreochromis niloticus. The fish samples undergo hot smoking after treatment with the spices, and data were analyzed using one-way ANOVA at a significance level of p
Keywords: African catfish; Nile tilapia; Profitability; Proximate analysis; Smoking; Spices